Knowledge, attitudes and practices (KAP) regarding menstruation among girls in Aurangabad, India and their correlation with sociodemographic factors - Deshmukh, Varsha; Sandhu, Gurpreet Kaur; Rachakonda, Laxmi; Kakde, Manisha; S. P., Andurkar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Menstruation has always been surrounded by different perceptions throughout the world. Nowadays, there is some openness toward menstruation, but differences in attitude still persist between different populations depending upon the education, socioeconomic status and the surroundings. We conducted this study to assess the knowledge regarding menstruation, their attitudes and the practises undertaken by the young girls of India .A prewritten questionnaire was distributed to these girls and the answers were analysed. Methods: A school based cross-sectional study design was employed in Aurangabad, Maharashtra. A multi stage sampling technique was used to select 1000 female high school and junior college and pharmacy college students. Data collection was carried out from May 2018 to August 2018 using a pre- tested structured questionnaire. The data were entered into a computer using Epi-info version 3.5.1 and then exported to SPSS for Windows version 20.0 for analysis. Bivariate and multivariate logistic regression analysis was done at 95 % confidence interval. Results: In this study 682and 552 respondents had good knowledge and practice of menstruation respectively. The findings of the study showed a significant positive association between good knowledge of menstruation and educational status of mothers (AOR = 1.51, 95% CI = 1.02-2.22), (AOR = 2.42, 95% CI:1.64-3.56). Educational status of the mother (AOR = 2.03, 95 % CI =1.38-2.97), revealed significant positive association with good practice and attitude of menstrual process. Conclusions: The findings showed that the knowledge and practice of menstruation is low. Hence awareness programmed should be conducted in schools regularly. Participation of mothers can also add to the knowledge and good practice scores of the young girls.